Production of Cysteine: Approaches, Challenges and Potential Solution - Ismail, Nur Izzah; Hashim, Yumi Zuhanis Has-Yun; Jamal, Parveen; Othman, Rashidi; Salleh, Hamzah Mohd (International Journal of Biotechnology for Wellness Industries, 2014)
Cysteine has a wide application in pharmaceutical, foods and cosmetic industries. In the biological system, through its unique properties of sulfur and thiol, cysteine also plays important roles in stability, structure, catalytic activity, and regulation of numerous proteins. In nature, cysteine can be found in animal proteins, fruits, vegetables, legumes and cereal. Due to its wide application, the production of cysteine in large scale is in favour. At present, cysteine is produced from keratin of animal sources as well as through microbial bioconversion and fermentation. Each production method poses its own challenges and limitation; which includes low yield, high-cost and poor consumer acceptance. As such, alternative source for large-scale cysteine production is of interest. Plants are seen to be an attractive substrate for the extraction of cysteine.